The Effect of Workload and Work Environment on Performance with Career Development as an Intervening Variable in PT. PLN (Persero) Implementation Unit North Medan Customer Service - M. Galeh Siddik; Kiki Farida Ferine; Sri Rahayu (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the effect of workload and work environment on employee performance, both directly and indirectly through career development as an intervening variable. The research was conducted on 69 respondents who are employees of a certain institution/company (institution name can be added if available). The analytical method used in this study is Partial Least Squares (PLS) with the assistance of SmartPLS software. The results show that workload has a positive and significant effect on employee performance but does not have a significant effect on career development. On the other hand, the work environment has a positive and significant effect on both career development and employee performance. Furthermore, career development also has a positive and significant effect on performance. In terms of indirect effects, the study found that career development does not mediate the relationship between workload and performance. However, it significantly mediates the relationship between the work environment and employee performance. These findings emphasize the importance of a supportive work environment and structured career development programs in enhancing employee performance. Organizations are encouraged to provide conducive working conditions and continuous development opportunities to optimize employee outcomes.